Engraftment of human mesenchymal stem cells in a severely immunodeficient mouse - Yuko Kato; Yusuke Ohno; Ryoji Ito; Takeshi Taketani; Yumi Matsuzaki; Satoru Miyagi (BMC, 2024)
Abstract The transplantation of human mesenchymal stromal/stem cells (hMSCs) has potential as a curative and permanent therapy for congenital skeletal diseases. However, the self-renewal and differentiation capacities of hMSCs markedly vary. Therefore, cell proliferation and trilineage differentiation capacities were tested in vitro to characterize hMSCs before their clinical use. However, it remains unclear whether the ability of hMSCs in vitro accurately predicts that in living animals. The xenograft model is an alternative method for validating clinical MSCs. Nevertheless, the protocol still needs refinement, and it has yet to be established whether hMSCs, which are expanded in culture for clinical use, retain the ability to engraft and differentiate into adipogenic, osteogenic, and chondrogenic lineage cells in transplantation settings. In the present study, to establish a robust xenograft model of MSCs, we examined the delivery routes of hMSCs and the immunological state of recipients. The intra-arterial injection of hMSCs into X-ray-irradiated (IR) NOG, a severely immunodeficient mouse, achieved the highest engraftment but failed to sustain long-term engraftment. We demonstrated that graft cells localized to a collagenase-released fraction (CR), in which endogenous colony-forming cells reside. We also showed that Pdgfrα+Sca1+ MSCs (PαS), which reside in the CR fraction, resisted IR. These results show that our protocol enables hMSCs to fulfill a high level of engraftment in mouse bone marrow in the short term. In contrast, long-term reconstitution was restricted, at least partially, because of IR-resistant endogenous MSCs.